THE IPV6 RESISTANCE - A SURVEY - Tr, Reshmi; K, Anusha; V, Sumathi; K, Pandiyarajan (Asian journal of pharmaceutical and clinical research, 2017)
Internet Protocol Version 6 (IPv6) was developed in 1990 to overcome the shortage of IP Version 4 (IPv4) addresses. The world saw IP Version 6 as the next generation IP addressing and an innovative backbone for the Internet. Although more than twenty five years have passed since the development of IPv6, but still IPv6 is seen as new technology without drastic enhancements and has not been widely adopted. Even Information Technology giants fear the network transition to IPv6 backbone. This article analyses the reason for this resistance towards IPv6. A detailed study of the same has been conducted and is discussed in the paper. The discussion includes the myths and facts that has resulted to the IPv6 resistance and outlines the resolutions for IPv6 transitions.